Problems and prospects of metal silos for grain storage in Western Nigeria (1997)
A survey involving the use of structured questionnaires and personal communication was carried out in Western Nigeria to ascertain the type and extent of use of silos for the storage of grains. Steel and Aluminium were found to be the predominant materials used for the construction of the silos. They are mainly used to store shelled corn and in a few instances, rice, cowpea and soybean. The prohibitive cost of silo acquisition limits their ownership and use to the Ministries of Agriculture, Co-operative Societies, agro-based industries, Teaching and Research Institutes and a few large scale private farms. Silos are not used by the small to medium scale farms. The withdrawal of the Ministries of Agriculture from direct grain production and the collapse of co-operative grain storage programmes have resulted in the abandonment of many silos. The metal silos experience the problem of moisture condensation on the roofs and walls which leads to the deterioration of stored grains through moulding, caking and rapid multiplication of insects. Losses of as much as 10% of total storage through these sources have been recorded for some silos. Adequate funding of current research efforts to develop local materials for grain silo construction is recommended.